Documents, reanalysis, and global circulation models: a new method for reconstructing historical climate focusing on present-day inland Tanzania, 1856–1890 - P. Gooding; M. J. Lazenby; M. R. Frogley; C. Dai; W. Su (Climate of the Past)
This article proposes a novel methodology for reconstructing past climatic conditions in regions and time periods for which there is limited evidence from documentary and natural proxy sources. Focusing on present-day inland Tanzania during the period 1856–1890, it integrates evidence from qualitative documentary sources with quantitative outputs from climate reanalysis and global circulation models (GCMs), which enables the creation of interdisciplinary seasonal time series of rainfall variability for three distinct locales. It does so by indexing each dataset to the same seven-point scale and weighting each output according to a predefined level of confidence in the documentary data. This process challenges the subjectivity of nineteenth-century Europeans in Africa, whose reports form the basis of the documentary material, and adds evidence from the region, which is currently lacking from the latest reanalysis products and GCMs. The result is an interpretation of documentary materials that is grounded in methods from both the humanities and natural sciences, as well as a more locally grounded estimation of rainfall that would otherwise be gained from referring to reanalysis or GCMs alone. The methodology is validated with reference to observed long-term trends gathered from (paleo)limnological studies and short-term trends gathered from documentary materials and instrumental records in nearby regions. It is shown to provide marked insights into four periods of environmental stress in the region's late nineteenth-century past. Future challenges may involve integrating evidence from oral traditions, which will require more in-region research and collaboration, and adapting the methodology for other regions and time periods.